Modelling Future Composite Indices for Nigerian Millennium Development Goals - Sa’idu, Bello Malam (Asian Journal of Economic Modelling, 2015)
This paper synthesized Millennium Development Goals (MDGs) progress by modelling future composite indices from the year 2016 to 2020 base on three out-of-sample results of forecasted models; Trend regression, Holt Exponential Smoothing, and Box-Jenkins. It applied a modified version of Malaysian Quality of Life index. The results revealed that there is aggregate progress across MDG composite indices of the models. Comparatively, MDG composite index of Trend regression is the highest among the models, followed by Holt Exponential Smoothing and then Box-Jenkins. The implication is that there is improvement in the aggregate MDG indicators, but the progression is too low or slow symbolizing oscillations not a straight line as assumed by MDG hypothesis. Consequently, more is needed to be done to fast-track MDG achievement. This work has originated Nigerian MDG composite indices computations, provided useful tools for policy analysis and public communications and basis for comparison among countries.